2012
DOI: 10.1088/0953-8984/24/32/325701
|View full text |Cite
|
Sign up to set email alerts
|

Strong-coupling topological Josephson effect in quantum wires

Abstract: Abstract. We investigate the Josephson effect for a setup with two lattice quantum wires featuring Majorana zero energy boundary modes at the tunnel junction. In the weak-coupling, the exact solution reproduces the perturbative result for the energy containing a contribution ∼ ± cos(φ/2) relative to the tunneling of paired Majorana fermions. As the tunnel amplitude g grows relative to the hopping amplitude w, the gap between the energy levels gradually diminishes until it closes completely at the critical valu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…For recent work on the fractional Josephson effect in the limits of strong tunneling and long junctions, see Refs. [115] and [116]. Experimental evidence of fractional AC Josephson effect in the form of doubled Shapiro steps has been reported in semiconductor Majorana wires [79].…”
Section: Fig 4 (Color Online)mentioning
confidence: 96%
“…For recent work on the fractional Josephson effect in the limits of strong tunneling and long junctions, see Refs. [115] and [116]. Experimental evidence of fractional AC Josephson effect in the form of doubled Shapiro steps has been reported in semiconductor Majorana wires [79].…”
Section: Fig 4 (Color Online)mentioning
confidence: 96%
“…where the wave vector k = {k x , k y }. In a finite system, the one-particle spectrum of the Hamiltonian H (1), (2), is also symmetric edge states including. The corresponding edge states are determined by the particle-hole states of Majorana fermions.…”
Section: Model Hamiltonian Edge Modesmentioning
confidence: 99%
“…As a promising experimental proof for the existence of MZMs, previous theoretical studies have suggested a fractional Josephson effect in a topological Josephson junction, where the Josephson current has a 4𝜋, rather than a 2𝜋, periodicity as a function of the phase difference between the two topological superconductors [4,[16][17][18][19][20][21][22][23][24][25]. The first paper presenting this idea is Ref.…”
Section: Introductionmentioning
confidence: 99%